Mandates of connection and guaranteed contracts transmission system: The application of the principle of free - Isasi Pastor, Carlos (2016)
This article has the objective to develop the general framework, previous knowledge and the analysis of the more important aspects related to the controversy that presents the collision of rules between a Connection Order, issued by the Osinergmin, and a Contract of the Guaranteed Transmission System, signed by the Peruvian state and a transmission licensee; that indeed present a unique situation in the energetic policy field.